Pathophysiology of COVID-19: Critical Role of Hemostasis - Andrade, Sonia Aparecida de; de Souza, Daniel Alexandre; Torres, Amarylis Lins; de Lima, Cristiane Ferreira Graça; Ebram, Matteo Celano; Celano, Rosa Maria Gaudioso; Schattner, Mirta; Chudzinski-Tavassi, Ana Marisa (Frontiers in Cellular and Infection Microbiology, 2022)
The COVID-19 pandemic, caused by SARS-CoV-2, had its first cases identified in late 2019 and was considered a clinical pandemic in March 2020. In March 2022, more than 500 million people were infected and 6,2 million died as a result of this disease, increasingly associated with changes in human hemostasis, such as hypercoagulation. Numerous factors contribute to the hypercoagulable state, and endothelial dysfunction is the main one, since the activation of these cells can strongly activate platelets and the coagulation system. In addition, there is a dysregulation of the renin-angiotensin system due to the SARS-CoV-2 takeover of the angiotensin converting enzyme 2, resulting in a strong immune response that could further damage the endothelium. Thrombus formation in the pulmonary microvasculature structure in patients with COVID-19 is an important factor to determine the severity of the clinical picture and the outcome of this disease. This review describes the hemostatic changes that occur in SARS-CoV-2 infection, to further improve our understanding of pathogenic mechanisms and the interaction between endothelium dysfunction, kallikrein-kinins, renin angiotensin, and the Coagulation/fibrinolysis systems as underlying COVID-19 effectors. This knowledge is crucial for the development of new effective therapeutic approaches, attenuating the severity of SARS-CoV-2’s infection and to reduce the deaths.